소비자의 쇼핑 동기가 온라인 쇼핑에 대한 신뢰도와 구매의도에 미치는 영향: 중국과 베트남 소비자를 중심으로 - 원성빈; 손증군; Won, Sung Bin; Sun, Zeng-Jun (한국콘텐츠학회 논문지, 16(8), 2016)
This study is based on the previous research which proved that "seeking convenience", "seeking low-cost" and "pleasures of shopping" are the major shopping motivation of online shopping. Research is conducted by using the trust as mediator, purchase intention as dependent variable. Also, differences between Chinese and Vietnamese consumers are applied in analysis of the model. The results were as follows: First, "seeking low-cost" and "pleasures of shopping" have positive effects on trust. Second, all shopping motivation have positive effect on purchase intention. Third, the trust has positive effect on purchase intention. Fourth, consumers' shopping motivation have significant difference in trust and purchase intention according to Chinese and Vietnamese consumers. The results of this study presented the strategic implications for operators at online shopping area. 본 연구는 전자상거래 및 온라인 쇼핑 분야의 선행연구를 토대로 소비자의 온라인 환경에서의 쇼핑 동기로 편의적, 쾌락적, 경제적 동기의 3가지 요인을 도출하여 온라인 쇼핑에 대한 신뢰도를 매개변수로, 구매의도를 종속변수로 연구모델을 설정하였다. 또한 중국과 베트남 2개 국가 소비자들의 성향차이를 조절변수로 설정하고 소비자의 쇼핑 동기가 온라인 쇼핑에 대한 신뢰도 및 구매의도에 미치는 영향을 분석하였다. 연구결과를 요약하면 다음과 같다. 첫째, 소비자의 쇼핑 동기 중 편의적 동기를 제외한 쾌락적, 경제적 동기 변수는 신뢰도에 정(+)의 영향을 미치는 것으로 분석되었다. 둘째, 소비자의 쇼핑 동기 중 모든 변수는 구매의도에 정(+)의 영향을 미치는 것으로 나타났다. 셋째, 온라인 쇼핑에 대한 소비자의 신뢰도는 구매의도에 정(+)의 영향을 미치는 것으로 검증되었다. 넷째, 소비자의 쇼핑동기가 온라인 쇼핑에 대한 신뢰도와 구매의도에 미치는 영향은 중국과 베트남 소비자에 따라 차이를 보이는 것으로 검증되었다. 본 연구결과를 토대로 중국시장과 베트남시장에 진출하는 기업들에게 현지화에 대한 실무적인 시사점을 제시하였다.